Is there a link between non-alcoholic fatty liver disease aspects and pancreatic cancer? Results of a case-matched study - REZENDE,ACHILES QUEIROZ MONTEIRO DE (2021)
ABSTRACT Background and Aims: An association between non-alcoholic fatty liver disease (NAFLD) and pancreatic ductal adenocarcinoma (PDAC) has been previously suggested. This study aims at investigating this association and at identifying potential links between variables of the NAFLD spectrum and PDAC. Methods: A cross-sectional case-matched analytical and comparative study was carried out to analyze patients undergoing surgical resection of PDAC and compare them to a control group of individuals undergoing cholecystectomy at a public tertiary teaching hospital, matched by sex, age and BMI. Hepatic histopathological examinations were compared between cases and controls. Results: Of 56 individuals, 36 were male (64.3%) and the median age was 61.5 years old (interquartile range: 57.5 - 70). The participants’ median BMI was 24.3 kg/m2 (interquartile range: 22.1-26.2 kg/m2). Microvesicular steatosis (p=0.04), hepatocellular ballooning (p=0.02), fibrosis (p=0.0003) and steatohepatitis (p=0.03) were significantly more frequent in the group of cases. Odds ratios for hepatocellular ballooning (6.2; 95%CI: 1.2-31.8; p=0.03), fibrosis (9.3; 95%CI: 2.5-34.1; p=0.0008) and steatohepatitis (3.9; 95%CI: 1.1-14.3; p=0.04) were statistically significant in relation to the PDAC prevalence. Conclusions: Significant associations were identified between histopathological aspects of NAFLD (microvesicular steatosis, hepatocellular ballooning, fibrosis, and steatohepatitis) and PDAC.